Selective Cu filling of nanopores using supercritical carbon dioxide. (10th April 2015) - Kondoh, Eiichi; Tamegai, Yukihiro; Watanabe, Mitsuhiro; Jin, Lianhua
Abstract: Supercritical fluid chemical deposition is known for its superior capability of filling metals into nanofeatures. The mechanism behind this filling capability has not been well understood and can be very different from those of other deposition techniques such as chemical vapor deposition. We have proposed a filling mechanism where the precursor condenses preferentially in narrow concave features and then converts into a metal deposit. In accordance with these two sequential phenomena, the narrower the feature is, the better the filling will be achieved. In this article, selective Cu deposition into nanopores of a silica-based porous thin film is described. When the conventional supercritical fluid deposition method was employed, a significant amount of Cu penetrated into the nanopores along with the continuous film formation on the substrate surface. By illuminating UV light before the start of Cu nucleation, Cu deposited selectively only inside the nanopores. During the selective deposition, optical changes in the porous film were investigated by in situ ellipsometry. These results indicate that the precursor condenses preferentially only in the nanopores and converts into a metal deposit.